PEMBUATAN COOKIES BERSERAT TINGGI DENGAN MEMANFAATKAN TEPUNG AMPAS MANGROVE (Sonneratiacaseolaris) (Jurnal Teknologi Pangan, 2013)
Demand of health food products such  as sugar-free foods, low-calorie diet and fiber-rich  increased. This trend is based on the role of prevention of hypertension, diabetes, colon cancer and  other  degenerative  diseases.  Various  sources  of  high-fiber  materials  such  as cellulose, hemicellulose, lignin, and  gum were a major  concern in  the  development  of food products. Therefore, the utilization of mangrove waste of syrup processing to yield a high fiber cookies  was  important  made.  This  study  aims  to  determine  the  proportion  of  wheat  and mangrove  waste  flour,   the addition  of margarine on  the  quality  of cookies.  This  study using Complete Randomized Design (CRD) factorial pattern with 2 factors and 3 replications. Factor I,  proportioni wheat flour: mangrove waste 15:85 (w/w), 30:70 (w/w), 45:55 (w/w). Factor II,the addition of margarine 40% (v/w), 45% (v/w), and 50% (v/w). The results showed that the best treatment was the proportion of wheat : mangrove waste flour 30:70 (w/w) and the addition of margarine 45% (v/b) which it produces cookies with the criteria  of 3.9343% moisture  content, protein 6.2745%, fat 22.4180%, and crude fiber value of 3.4456%.Key words: cookies, mangrove waste, health food products